PENERAPAN MODEL PEMBELAJARAN CONTROVERSIAL ISSUES (CONTROLIS) MATERI DINAMIKA PERAN INDONESIA DALAM PERDAMAIAN DUNIA UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS DAN HASIL BELAJAR SISWA KELAS XI IPS 4 SMA NEGERI 1 LASEM - Suwito, Anton (CV Sintesia, 2025)
Citizenship Education Subject aims for students to have the following abilities: Think critically, rationally, and creatively in response to citizenship issues, participate actively and responsibly, and act intelligently in social, national and state activities, and anti -corruption, developing in a positive and democratic manner to shape oneself based on the characteristics of Indonesian society so that they can live together with other nations, interact with other nations in the world arena directly or indirectly by utilizing information and communication technology. The controlist learning model emphasizes the approach to controversial issues. Controlis learning model aims to improve or improve the quality of the learning process in the classroom, to determine the increase in students' critical thinking skills in the PPKn subject. The controlist learning model in this study aims to improve critical thinking skills and the achievement of student learning outcomes. Achievement of learning outcomes in the initial conditions of learning towards cycle 1 is the lowest value decreases by 10% from UH 1 48 to 38 and UH 2 decreases 18% from a value of 64 to 46, the highest value has increased from UH 1 95 to UH 2 97. The average value increases by 40% from 75 to 79 and the value from 79 to 83. In cycle 1, UH cycle 1 the lowest value is UH1 = 38 UH2 = 46, the highest value is UH1 = 95 and UH 2 97 The mean value of UH 1 = 79 and UH 2 = 83. In cycle 2 the lowest value is UH1 = 18 and UH 2 = 46, the highest value is UH1 = 85 and UH 2 = 90 The mean value of UH1 = 59 and UH 2 = 74. In this classroom action research using comparative descriptive analysis in determining the value between cycles.